Why some carbons may or may not graphitize? The point of view of thermodynamics. (August 2019) - Ouzilleau, Philippe; Gheribi, Aïmen E.; Chartrand, Patrice; Soucy, Gervais; Monthioux, Marc
Abstract: Not all carbons graphitize in equal measure. Some will develop a structure which approaches the one of perfect graphite (graphitizable carbons) upon heat treatment, while others will not (non-graphitizable carbons). The present work develops a phenomenological model for the conceptual understanding of graphitizability (capacity to graphitize). To support this model, a mathematical formalism, inspired from thermodynamics, is proposed to calculate the Ultimate Graphitizability ( η g ) of some graphitizable and non-graphitizable carbon materials. η g is the average interlayer spacing ( d 002 ) of a graphenic carbon following graphitization at ∼ 3400 K . η g can be estimated assuming a topological graphitization mechanism operating between 1700 K and 3400 K . Two independent variables define η g : d 002 ( T α ) and d 002 ( T β ) . T α and T β are arbitrarily selected temperatures between 1700 K and 2550 K (the graphitization threshold). In order to better understand the parameters affecting d 002 ( T α ) and d 002 ( T β ), new carbonization/graphitization experimental results are presented. These suggest that d 002 ( T α ) and d 002 ( T β ) are correlated to the oxygen/hydrogen composition ratio and the relative mesoscale crystallite orientation of some graphitizable carbons following the end of primary carbonization. Graphical abstract: Image 1